Assisted Conception and South Asian communities in the UK: public perceptions of the use of donor gametes in infertility treatment. (March 2013) - Culley, Lorraine; Hudson, Nicky; Rapport, Frances
Abstract This paper explores 'public' attitudes to the use of donated gametes in infertility treatment amongst members of British South Asian communities in the UK. The study included 14 single-sex focus groups with a total of 100 participants of Indian, Pakistani and Bangladeshi origins in three English cities and 20 individual semi-structured interviews with key informants. It explores five themes from the data: childlessness and stigma; using sperm and using eggs; cultural connections; choosing gametes; religion and the use of donated gametes; and disclosure and the management of information. The paper demonstrates that the socio-cultural context of fertility treatment is highly relevant and those delivering services and those consulting the public need to be aware of cultural and gender differences. Third party assisted conception represents a challenge to received ideas of identity and has implications for social reproduction and kinship which go well beyond immediate conjugal relationships.